ADAPTASI WANITA ISLAM TERHADAP KELUARGA SUAMI Studi Kasus Perkawinan Amalgamasi Wanita Islam dan Pria Hindu di Bali - Diah Dharmapatni, Desak Putu (Humanis; Volume 15. No.1. April 2016, 2016)
Marriage in Bali usually match the balinese Hinduism couple. Nowadays, some Hinduism men marry Moslem women in Bali. According to Hinduism, the Moslem woman must convert her religion to be an Hinduism and do balinese tradition. The moslem woman must adapt herself and the environment in order to do her new tradition. She do some adaptation strategy in learning balinese language, cooking, dressing, making banten and menyama braya. Adaptation strategy are plan and which she do in order to attract attention in the husband family. This research describe adaptation strategy of the moslem woman in the husband family and the impact in her life.
Keywords: Adaptation, Marriage, Amalgamation